Numerical comparison between DPSK 33, DPSK 66 and duo binary in WOC system - Mustafa H. Ali; Hazim M. Ali; Tariq A. Hassan (Institute of Advanced Engineering and Science, 2021)
OWC systems have turned into a state-of-the-art technology because of their superior performance uniqueness and its innumerable characteristic as compared to its RF. One of the OWC application is inter-satellite wireless optical communication (Is-WOC), this framework can be improved by using different ways such as advanced modulation formats and aperture diameter. We demonstrate an analysis based on the aperture diameter effect in transmission of single channel with 40 Gb/s Is-WOC system using three different modulation methods, differential phase-shift keying (DPSK) with a duty ratio to 66% and 33% and duobinary. Choosing these three modulations from various modulation format is done depending on the advantage they provide where the DPSK gives to fiber nonlinearity a powerful robustness and less susceptible to SPM and XPM and for system requirements of dispersion compensation in duobinary, it provides higher chromatic dispersion tolerance mitigate. The result shows the effect of different transmitter aperture diameter (from 2 to 20 cm) for a constant distance 200 km accomplished by quality factor and minimum BER. We conclude there is a great loss in the small aperture diameter, even in the presence of best modulation format, therefore as the aperture diameter increase the Q-factor increase, but some increased rise is linear and the other is changing from linear to non-linear in a fixed Q-factor point equal to 5.63.